# Prove that abcababcabc(a¯+2b¯-c¯).[(a¯-b¯)×(a¯-b¯-c¯)]=3[a¯b¯c¯]. - Mathematics and Statistics

Sum

Prove that (bar"a" + 2bar"b" - bar"c"). [(bar"a" - bar"b") xx (bar"a" - bar"b" - bar"c")] = 3 [bar"a" bar"b" bar"c"].

#### Solution

(bar"a" + 2bar"b" - bar"c"). [(bar"a" - bar"b") xx (bar"a" - bar"b" - bar"c")] = 3 [bar"a" bar"b" bar"c"]

= (bar"a" + 2bar"b" - bar"c").(bar"a"xxbar"a" - bar"a" xx bar"b" - bar"a" xx bar"c" - bar"b" xx bar"a" + bar"b" xx bar"b" + bar"b" xx bar"c")

= (bar"a" + 2bar"b" - bar"c").(bar"0" - bar"a" xx bar"b" - bar"c" xx bar"a" - bar"a" xx bar"b" + bar"0" + bar"b" xx bar"c")

= (bar"a" + 2bar"b" - bar"c"). (bar"c" xx bar"a" + bar"b" xx bar"c")

= bar"a".(bar"c" xx bar"a") + bar"a".(bar"b"xxbar"c") + 2bar"b".(bar"c" xx bar"a") + 2bar"b".(bar"b"xxbar"c") - bar"c".(bar"c" xx bar"a") - bar"c".(bar"b" xx bar"c")

= 0 + bar"a".(bar"b" xx bar"c") + 2bar"b".(bar"c" xx bar"a") + 2 xx 0 - 0 - 0

= [bar"a"  bar"b"  bar"c"] + 2[bar"b"  bar"c"  bar"a"]

= [bar"a"  bar"b"  bar"c"] + 2[bar"a"  bar"b"  bar"c"] = 3[bar"a"  bar"b"  bar"c"]

Concept: Vector Triple Product
Is there an error in this question or solution?